Review of: Dimitris Dimitropoulos, Christos Loukos and Panagiotis Michailaris (eds.),ΌΨΕΙΣ ΤΗΣ ΕΠΑΝΑΣΤΑΣΗΣ ΤΟΥ 1821: ΠΡΑΚΤΙΚΑ ΣΥΝΕΔΡΙΟΥ,ΑθΗΝΑ 12 ΚΑΙ 13 ΙΟΥΝΙΟΥ 2015 [Facets of the 1821 Revolution: Conference Proceedings, Athens, 12–13 June 2015], Athens: Society for the Study of Modern Hellenism–Mnimon, 2018, 404 pages. - Sarafis, Vangelis (The Historical Review/La Revue Historique, 2020)
.